PROGESTERONE IMPREGNATED VAGINAL SPONGE IS BETTER COMPARED TO INJECTABLE PROGESTERONE FOR THE INDUCTION OF ESTRUS IN GOAT - DASH, S; MOHANTY, D N; JENA, B (The Indian Journal of Animal Reproduction, 2016)
Healthy breedable does were synchronized for estrous either with natural progesterone impregnated intravaginal sponges (AVIKESIL-S, for 15 days in situ, n=20) or long acting progesterone (50 mg, 0.2 ml/doe, i.m., P-Depot, n=20) at an interval of 3 days for 5 occasions. Both the group of does received 125 μg cloprostenol on the day of sponge withdrawal or after the completion of injectable progesterone treatment. Another group of does (n=20) were maintained under routine managemental practices without any hormonal treatment. In brief, the does treated with vaginal sponge had better exhibition of estrus as compared to other does.
Keywords: Doe; Estrous synchronization; Intravaginal Sponge; PGF2α; Progesterone